Pengaruh Reward dan Punishment Terhadap Kinerja Karyawan Pada Bandara Internasional Hotel Tangerang Banten - Sigit Purnomo; Arman Syah; Budhi Prabowo; Elizabeth Tika Kristina Hartuti (Peneliti.net, 2021)
The purpose of this study was to determine the effect of Reward on Employee Performance, the effect of Punishment on Employee Performance, and to determine the effect of Reward and Punishment together on Employee Performance at the International Airport Hotel. The research methodology used by the author is quantitative methods, data collection methods by distributing questionnaires which are then processed using regression analysis. The population and sample in this study were all employees at the International Airport Hotel with a total of 98 employees. While the data analysis used in the form of validity and reliability tests. Linear regression test, correlation test, determination test and hypothesis testing using t test (partial), F test (simultaneous).The results of the research on the correlation test of 0.921 which shows that there is a very strong relationship and the value of determination is 0.848, meaning that the contribution of Reward and Punishment variables on Employee Performance is 84.8%. The simple linear regression test is Y=3.372+0.642X1 and Y=3.774+0.914X2, meaning that the increase in the Reward variable on Employee Performance is 0.642 or 64.2% and the increase in the Punishment variable on Employee Performance is 0.914 or 91.4%.The results of the t-test (partial) for the Reward variable have a t-count value of 3.159 > t-table 1.665 and a value of 0.002 <0.05 and the Punishment variable has a t-value of 8.214 > t-table 1.665 with a significant value of 0.000 <0.05. Based on the results of the F test (simultaneous) F-count 265.856 > F-table 3.09 and a significant value of 0.000 <0.05, it can be concluded that Ho3 is rejected and Ha3 is accepted. This means that the Reward and Punishment variables simultaneously have a significant effect on Employee Performance at the International Airport Hotel.